40. Event related potentials recorded by intracerebral electrodes. Issue 12 (December 2017) - Pro, S.; Specchio, N.; De Palma, L.; Marras, C.E.; Fusco, L.; Vigevano, F.; Valeriani, M.
Abstract : Preoperative evaluation, by means of intracerebral electrodes, in patients presenting with symptomatic drug resistant epilepsy, provides an opportunity to explore neural generators of P300, Mismatch Negativity (MMN) and also N140. We studied 5 pediatric patients with drug resistant epilepsy. ERPs and SEPs (to median and tibial nerve stimulation) were recorded from the intracerebral electrode contacts referred to the earlobe ipsilateral to the stimulation. P300 was recorded by electrodes located in hippocampus with a clear inversion of signals in posterior hippocampus; MMN was also well recorded by electrodes placed in opercular-insular cortex without a clear inversion of signal; N140, increased in amplitude during attention condition, showed the maximum amplitude in the frontal electrode contacts and in the opercular-insular traces. Numerous investigations revealed that generators of Event Related Potentials are independent and also with a cortical-subcortical distribution. In this short case series, we could show some brain areas clearly involved in the generation of P300, MMN and N140 components.